Risk Factors Associated with Angiographic Severity of Coronary Artery Disease Based on Serum Uric Acid: A Study in a Tertiary Care Hospital, Chattogram, Bangladesh - Ismail, Khondaker M; Sadaf, Anika; Das, Saurav; Latif, Sayem Bin; Rahman, Mohammad Mostafijur; Eva, Tania Easmin (IAHS Medical Journal, 2024)
Background: Coronary Artery Disease (CAD) is a leading cause of death worldwide, identifying risk factors and severity is crucial for management and prevention. Serum Uric Acid (SUA) has been proposed as a potential marker for the severity of CAD. Elevated SUA levels are associated with endothelial dysfunction, oxidative stress, and inflammation, all of which contribute to the development and progression of atherosclerosis. This study aims to determine the association of risk factors with the severity of CAD using SUA levels. Materials and methods: This was a cross-sectional observational study conducted in the Department of Cardiology at CMCH in Chattogram over one year from October 2020 to September 2021. After case selection demographic data were collected and transthoracic echocardiography was performed on study patients. Results: The study analyzed the association between SUA level and CAD severity in 130 patients undergoing coronary angiography. The mean SUA level was 5.06 mg/dl and was significantly associated with the presence of CAD, number of vessel involvement and severity of CAD assessed by the Gensini score. The mean SUA level in cases with CAD was significantly higher (5.26 ± 1.32 mg/dl) than in cases without CAD (4.22 ± 1.03 mg/dl). Conclusion: This study concluded that demographic variables and risk factors are associated with the severity of CAD. The severity of CAD was higher in elderly and male patients. The study suggests that when assessing the risk in a CAD patient, hyperuricemia should be considered. IAHS Medical Journal Volume 6(2) December 2023; 48-52